Heavy metal removal from water using the metallogelation properties of a new glycolipid biosurfactant. Issue 2 (8th November 2022) - Poirier, Alexandre; Ozkaya, Korin; Gredziak, Julie; Talbot, Delphine; Baccile, Niki
Abstract: Water pollution by heavy metals is a problem in both western and developing countries. Heavy metal pollution can be associated with human activity, such as wastewaters from processing of ore mining, but also to simple contamination from metal‐rich soils. Whichever the case, chemical and physical methods are generally employed to depollute water. Since most chemicals are themselves polluting agents, there is an increasing interest in finding biobased and biodegradable alternative chemicals, both efficient in removing metals and benign to the environment. Biosurfactants are green chemicals produced by fermentation of yeasts and bacteria and with a good environmental score. Among many applications, this class of compounds has been used to remove heavy metals from contaminated soils. Within this framework, we propose a new mechanism of depolluting water using a glucolipid biosurfactant, G‐C18:1, composed of glucose (G) and a C18:1 fatty acid (oleic acid). This compound is able to form a metallogel by complexing cations in water, thus trapping heavy metals (Cu 2+, Ni 2+, Cr 2+, and Co 2+ ) in the gel phase. This mechanism allows to remove up to 95% for cobalt and 88 ± 10%, 80 ± 3%, and 59 ± 6% for Cu 2+, Ni 2+, and Cr 2+, respectively. A dedicated structural study shows that this is possible because positively charged species induce gelation of G‐C18:1 through a micelle‐to‐wormlike phase transition, most likely driven by a charge neutralization process. This work shows that wise control of the nanoscale properties of green chemicals can strongly benefit to develop a sustainable future.